2020
DOI: 10.1016/j.agwat.2020.106039
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study and multi–objective optimization for drip irrigation of grapes in arid areas of northwest China

Abstract: Grapes are the most important cash crop in Xinjiang. However, the effective utilization of agricultural water and fertilizer in this area is relatively low, which is very unfavourable for the development of Xinjiang grape industry. At present, there is a lack of research based on multi-objective water and fertilizer optimization to guide grape production. Field experiments were thus conducted over three consecutive years (2015)(2016)(2017) to study the effects of water and fertilizer coupling on the yield, fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 28 publications
(8 reference statements)
1
5
0
1
Order By: Relevance
“…These values are in agreement with other studies performed over table grapes (e.g. FAO, 2019;Li et al, 2020).…”
Section: Tablesupporting
confidence: 93%
See 1 more Smart Citation
“…These values are in agreement with other studies performed over table grapes (e.g. FAO, 2019;Li et al, 2020).…”
Section: Tablesupporting
confidence: 93%
“…The fruit yield (FY) for two cultivars are inside the range of what is produced (14-18 t/ha) in Costa de Hermosillo, northwest Mexico, following the statistical data , 2018). The grapes yield production depends mainly on the irrigation water supply and fertilization (Li et al, 2020).…”
Section: Study and Data Descriptionmentioning
confidence: 99%
“…The binary quadratic regression equation was established with water and fertilizer inputs as independent variables and the comprehensive quality, yield, IWUE, PFP, and net profits of fragrant pear as dependent variables [43,44], as shown in Table 9. The regression analysis showed that the effects of water and fertilizer inputs on the indicators reached a highly significant level (p < 0.01), and the coefficients of determination were > 0.85 (Table 9).…”
Section: Multi-objective Solution For Optimal Water and Fertilizer Am...mentioning
confidence: 99%
“…Segundo Tan e Nasurdin (2010) e Li et al (2020), as variáveis climáticas presentes no dia a dia da agricultura, em grande parte das vezes são incontroláveis, geram a necessidade de soluções criativas que auxiliam os produtores a quantificarem e trabalharem com as demais instabilidades de seus negócios. Trazendo assim, elevada importância tanto para o desenvolvimento dos grandes produtores como também para manutenção da agricultura familiar.…”
Section: Referencial Bibliográficounclassified